Encyclopedia of Life Sciences 2014
DOI: 10.1002/9780470015902.a0025581
|View full text |Cite
|
Sign up to set email alerts
|

Structure–Function Relationships in the Aromatic Amino Acid Hydroxylases Enzyme Family: Evolutionary Insights

Abstract: The nonheme iron and tetrahydrobiopterin dependent aromatic amino acid hydroxylases (AAAHs) comprise a family of enzymes that catalyse the hydroxylation of l ‐Phe, l ‐Tyr and l ‐Trp. These reactions are of central physiological importance. Consequently, dysfunction of the AAAHs is associated with serious disorders, that is, the genetic metabolic disease phenylketonuria for phenylalanine hydroxylase (PAH), and neurological and n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
10
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 60 publications
1
10
0
Order By: Relevance
“…The aromatic amino acid hydroxylases (AAAHs) are a family of non‐heme iron‐ and tetrahydrobiopterin (BH 4 )‐dependent enzymes that catalyze the hydroxylation of their respective aromatic amino acid substrates using O 2 as an additional substrate (Fitzpatrick, ; Skjærven, Teigen, & Martinez, ). In vertebrates, four genes code for the AAAHs: phenylalanine hydroxylase ( PAH ), tyrosine hydroxylase ( TH ), and tryptophan hydroxylases 1 and 2 ( TPH1 and TPH2 ).…”
Section: Introductionmentioning
confidence: 99%
“…The aromatic amino acid hydroxylases (AAAHs) are a family of non‐heme iron‐ and tetrahydrobiopterin (BH 4 )‐dependent enzymes that catalyze the hydroxylation of their respective aromatic amino acid substrates using O 2 as an additional substrate (Fitzpatrick, ; Skjærven, Teigen, & Martinez, ). In vertebrates, four genes code for the AAAHs: phenylalanine hydroxylase ( PAH ), tyrosine hydroxylase ( TH ), and tryptophan hydroxylases 1 and 2 ( TPH1 and TPH2 ).…”
Section: Introductionmentioning
confidence: 99%
“…Together with phenylalanine hydroxylase (PAH) and tyrosine hydroxylase (TH), Tph belongs to the family of pterin-dependent aromatic amino acid hydroxylases (AAAHs), having BH 4 and O 2 as co-substrates and Fe 2+ as cofactor. Crystallographic and mutagenesis studies have shown that AAAHs are characterized by three main functional regions: a regulatory N-terminal region, a catalytic domain, which contains the cofactor and substrate binding sites, and the C-terminal leucine zipper tetramerization domain [ 3 5 ]. Despite Tphs have a protein sequence homology of 71%, Tph2 has 44 additional aminoacidic residues at its N-terminus, which are not present in Tph1 [ 1 ].…”
Section: Introductionmentioning
confidence: 99%
“…TH belongs to the BH 4 -dependent aromatic amino acid hydroxylases (AAAH), a family of enzymes that catalyze physiologically and medically important reactions. Phenylalanine hydroxylase (PAH) and tryptophan hydroxylase 1 and 2 (TPH1 and TPH2) are the rate-limiting enzymes in the degradation of excess L-phenylalanine and the production of serotonin, respectively 3 . The three enzymes are homotetramers, with each subunit consisting of a regulatory ACT domain with an unstructured N-terminal tail of different length, a catalytic domain including the iron coordinated to a 2-His-1-carboxylate facial triad motif 4 , and an oligomerization domain 3 5 .…”
mentioning
confidence: 99%
“…Phenylalanine hydroxylase (PAH) and tryptophan hydroxylase 1 and 2 (TPH1 and TPH2) are the rate-limiting enzymes in the degradation of excess L-phenylalanine and the production of serotonin, respectively 3 . The three enzymes are homotetramers, with each subunit consisting of a regulatory ACT domain with an unstructured N-terminal tail of different length, a catalytic domain including the iron coordinated to a 2-His-1-carboxylate facial triad motif 4 , and an oligomerization domain 3 5 . For PAH, structures of the full-length tetramer from rat were recently solved 6 7 but for TH, only truncated forms are available.…”
mentioning
confidence: 99%
See 1 more Smart Citation